CONNOR AND THE TAEKWONDO TOURNAMENT - Malia, Jen; Francis, Peter (Minneapolis, MN : Beaming Books, 2024)
Perseverance, thought Connor. To not give up even when it is hard to keep going. Connor loves practicing taekwondo at his dojang. Having ADHD means he has to work a little harder to keep his focus during sparring sessions, but that doesn't stop him from mastering new forms and rising through the taekwondo ranks. However, when Wyatt-Connor's nemesis-starts training at the same dojang, staying focused suddenly becomes a lot harder. Can Connor persevere and find his focus in time for the big tournament? Written by a neurodivergent author with three neurodivergent children, Connor and the Taekwondo Tournament meets a longstanding need for chapter books written from the perspectives of kids with ADHD and is the perfect addition to any young reader's shelf. The Infinity Rainbow Club is a chapter book series featuring five neurodivergent children in a club at their elementary school. The club provides a safe space for stims and different communication styles to be accepted and celebrated.
Ages: 7-10.
Keywords: Attention-deficit hyperactivity disorder -- Fiction; Taekwon do -- Fiction; Friendship -- Fiction